2022
DOI: 10.1002/ps.7004
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of acyl‐ACP thioesterase as site of action of the commercial herbicides cumyluron, oxaziclomefone, bromobutide, methyldymron and tebutam

Abstract: BACKGROUND: Understanding the mode and site of action of a herbicide is key for its efficient development, the evaluation of its toxicological risk, efficient weed control and resistance management. Recently, the mode of action (MoA) of the herbicide cinmethylin was identified in lipid biosynthesis with acyl-ACP thioesterase (FAT) as the site of action (SoA). Cinmethylin was registered for selective use in cereal crops for the control of grass weeds in 2020.RESULTS: Here, we present a high-resolution co-crysta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Cumyluron is also a FAT-inhibiting herbicide (Johnen et al 2022) that controls annual bluegrass before it emerges (Askew and McNulty 2014; Reicher et al 2015). Limited peer-reviewed information exists regarding cumyluron usage; however, the patent indicates that it inhibits annual bluegrass germination at rates of 500 to 30,000 g ai ha –1 (Tomita and Tonaka 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Cumyluron is also a FAT-inhibiting herbicide (Johnen et al 2022) that controls annual bluegrass before it emerges (Askew and McNulty 2014; Reicher et al 2015). Limited peer-reviewed information exists regarding cumyluron usage; however, the patent indicates that it inhibits annual bluegrass germination at rates of 500 to 30,000 g ai ha –1 (Tomita and Tonaka 2003).…”
Section: Introductionmentioning
confidence: 99%
“…With a library of 28 compounds in hand (Table ), we evaluated them in a series of in vitro assays to determine whether they inhibited any known herbicidal targets. We observed that the thiazolopyridines 8a-8ab inhibited acyl-ACP thioesterase (FAT) in a fluorescence polarization (FP) assay, thus this new compound class exhibits in vitro inhibitory activity against the same site of action (SoA) as the commercial herbicides cinmethylin, methiozolin and oxaziclomefone . From the pI 50 values obtained, we were able to understand more about the SAR of the thiazolopyridine class with regard to its inhibitory activity against the FAT A protein.…”
Section: Resultsmentioning
confidence: 99%
“…We observed that the thiazolopyridines 8a-8ab inhibited acyl-ACP thioesterase (FAT) in a fluorescence polarization (FP) assay, thus this new compound class exhibits in vitro inhibitory activity against the same site of action (SoA) as the commercial herbicides cinmethylin, 21 methiozolin 36 and oxaziclomefone. 37 From the pI 50 values obtained, we were able to understand more about the SAR of the thiazolopyridine class with regard to its inhibitory activity against the FAT A protein. When comparing the thiazolopyridines 8a−8k, we observed that the highest inhibitory pI 50 values against FAT A were obtained when the phenyl ring in the R 1 position was bearing a small substituent in the ortho position, such as the compounds 8b, 8e and 8g (Table 2).…”
Section: Journal Of Agricultural and Food Chemistry Pubsacsorg/jafc A...mentioning
confidence: 99%
“…Six commercial herbicides (HRAC group 30), including cinmethylin, target this enzyme. 163,164 FATs are also required for fatty acid production in fungi. 165,166 We have found no literature on the effects of these herbicides on fungi.…”
Section: Found In Fungi That Are Not Commercial Fungicide Targetsmentioning
confidence: 99%
“…Because FATs have not been annotated in the B. cinerea genome yet, this target is not included in Table . Six commercial herbicides (HRAC group 30), including cinmethylin, target this enzyme. , FATs are also required for fatty acid production in fungi. , We have found no literature on the effects of these herbicides on fungi. However, the natural microbial metabolite cerulenin inhibits this enzyme in both fungi ( S. cerevisiae ) and plants. , Cerulenin was first mentioned as an antifungal antibiotic and later reported to be phytotoxic .…”
Section: Target Sites Of Commercial Herbicides Found In Fungi That Ar...mentioning
confidence: 99%